The picky eagle how democracy and xenophobia limited U.S. territorial expansion - Maass, Richard W. (Ithaca Cornell University Press, 2020)
"This book explains why the United States stopped annexing territory by focusing on annexation's domestic political and normative consequences"--
The limits of U.S. territorial expansion -- Explaining annexation -- To the continent : European empires and U.S. annexation -- To the west : Native American lands and U.S. annexation -- To the north : Canada and U.S. annexation -- To the south : Mexico and U.S. annexation -- To the seas : islands and U.S. annexation -- To the world : the international implications of U.S. annexation
Print version record
Includes bibliographical references and index
JSTOR
Keywords: Democracy -- United States -- History; Xenophobia -- Political aspects -- United States -- History; United States -- Territorial expansion -- History; United States -- Foreign relations; Xénophobie -- Aspect politique -- États-Unis -- Histoire; États-Unis -- Expansion territoriale -- Histoire; États-Unis -- Relations extérieures.; HISTORY -- United States -- Revolutionary Period (1775-1800); Democracy; Diplomatic relations; Territorial expansion; United States; International Relations, Diplomatic History, US History, US Foreign Policy, International Security; Electronic books; History